Transcriptome Analysis Reveals Key miRNA–mRNA Pathways in Ovarian Tissues of Yunshang Black Goats With Different Kidding Numbers - Liu, Yufang; Zhou, Zuyang; Guo, Siwu; Li, Kunyu; Wang, Peng; Fan, Yekai; He, Xiaoyun; Jiang, Yanting; Lan, Rong; Chen, Shuangzhao; Dai, Shenghong; Hong, Qionghua; et al. (Frontiers in Endocrinology, 2022)
Ovarian tissue is an important reproductive organ for mammalian reproduction, and which constructed by the smallest structural unit was follicle. The granulosa cell (GC) was a basic functional unit of follicle, and it was important for promoting follicle growth and the sex hormones and growth factors secretion in the process of reproduction. The proliferation of GCs is accompanied by the secretion of sex hormones (progesterone and estrogen) to create the microenvironment for ovulation in the oocyte. A variety of factors influence granulocyte proliferation, yet there are still many gaps to be filled in the targets and non-coding RNA regulation. In our study, the differential expression mRNAs and miRNAs were detected by using RNA-seq, and constructed a mRNA-miRNA network related to the prolificacy in goat. Then, the goat primary GCs were isolate from the follicle for the function validation of candidate genes and its regulator miRNA. A total of 2,968 differentially expressed (DE) mRNAs and 99 DE miRNAs were identified in the high- and low- prolificacy goat by RNA-seq. JAK3 were identified highly expressed in the low prolificacy goats (was 3 times than high prolificacy goats), and the integrate analysis showed that chi-miR-493-3p was a potential regulator of JAK3. The PI3K-Akt signaling pathway was a typical pathway for cell proliferation, differentiation, apoptosis and migration. We found that the chi-miR-493-3p targets to JAK3 directly via RT-qPCR, dual fluorescence assays and western blot. Furthermore, the expression of JAK3 was significantly decreased by the chi-miR-493-3p mimic and increased by the chi-miR-493-3p inhibitor. The CCK-8 assay showed that overexpression of JAK3 promoted cell proliferation, while inhibiting JAK3 had the opposite effect. The expression of cell proliferation marks CDK4 and cyclin D2 also showed the same results. Moreover, the enzyme-linked immunosorbent assay showed that steroid hormones E2 and PROG were increased by overexpressed JAK3, and decreased by inhibiting JAK3. Therefore, our results identified a chi-miR-439-3p-JAK3 regulatory pathway, which provided a new insight for the granulosa cell proliferation and prolificacy of goat.